Empowering Mangrove Ecotourism: Integrating Governance, Community, and Technology for Sustainable Coastal Development - Mardianton, Mardianton; Amar , Syamsul; Irianto , Agus (Journal of Ecohumanism, 2024)
This study uniquely explores the under-researched synergy between institutional governance, community engagement, and technology utilization in sustainable mangrove ecotourism, specifically in Pesisir Selatan Regency. Addressing gaps in the literature, it evaluates how institutional frameworks and local participation impact conservation amidst the rapid growth of tourism in the region. Using a quantitative approach, data were gathered from 395 respondents living near mangrove ecotourism sites. Structural Equation Modeling (SEM) revealed that robust governance and active community involvement significantly contribute to sustainable ecotourism. However, technological adoption remains constrained due to inadequate infrastructure and low digital literacy. The findings highlight the need to enhance technological infrastructure to maximize its conservation potential. This comprehensive analysis underscores the importance of harmonizing institutional policies and community involvement while leveraging technology to support conservation. The study's insights are not only relevant to the local context but also offer a framework for other coastal regions facing similar challenges. Empowering communities, reinforcing governance, and investing in technological advancements are essential steps toward sustainable ecotourism, fostering economic benefits while safeguarding coastal ecosystems for future generations.